Power Grid Frequency Regulation Strategy for Photovoltaic Plant Based on Multi-Objective Harris Hawks Optimization - Wang, Long; Chang, Xucheng; Li, Xiang; Huang, Wenli; Jiao, Yingying (Frontiers in Energy Research, 2021)
To settle the issue of balance between two objectives, i.e., photovoltaic (PV) power station output power maximization and frequency regulation (FR) signals response, a novel PV reconfiguration strategy is proposed in this work, which maximizes the output power through PV reconfiguration, and meanwhile utilizes the energy storage system (ESS) to decrease the PV plant generated power’ deviation from FR signals. Above all, a model of PV-storage power station reconfiguration is designed to minimize the power bias of both rated power and FR signals. Then, the multi-objective Harris hawks optimization (MHHO) is used to obtain the Pareto front which satisfies the above two objectives due to its high optimization efficiency and speed. Subsequently, the optimal compromise solution is selected by the decision-making method of VIseKriterijumska Optimizacija I Kompromisno Resenje (VIKOR). Aiming to substantiate the efficacy of the proposed technique, the case study is carried out under partial shading condition (PSC) with time-varying FR signal. The simulation results show that, compared with the situation without optimization, the power deviations of the two objectives are reduced by 23.27% and 55.81% respectively by proposed method.